The Influence of Digital Financial Literacy, Perceived Ease of Use, Perceived Usefulness, Social and Political on The Intention and Use Behavior of Using QRIS as a Payment System in Traditional Retail - Asaif, Jimly Majidi; Suripto, Suripto; Wardianto, Kussuyatmono Bagus; Wulandari, Jeni (Eastasouth Institute, 2025)
The presence of QRIS in traditional retail in Pringsewu Regency as one of the digital payment systems is part of the steps to support the National Non-Cash Movement (GNNT). This study aims to determine the direct influence of digital financial literacy, perception of convenience, perception of benefits, social and political on the intention and behavior of using QRIS as a payment system in traditional retail (study on traditional retail in Pringsewu Regency). This type of research is explanatory research using a quantitative approach. The data obtained from the questionnaire consisted of 23 questions and were submitted to 105 respondents, then analyzed using SmartPLS, so that the results of the study were in the form of relationships between the variables being compared. The results of this study indicate that the variables of digital financial literacy, perception of benefits, and politics do not significantly influence the intention to use QRIS. However, the variables of perception of convenience and social have a significant effect on behavioral intentions. While the variable of intention to use QRIS is known to have a significant influence on the behavior of using QRIS in traditional retail in Pringsewu Regency. The implications of this study support the cultivation of a digital-based economic system. There is a need to be supported with the development of technological infrastructure, such as expanding internet access, switching to a digital-based payment system, modernizing traditional retail, and so on. In order to be realized, contributions from various parties and related policy makers are needed so that this multidisciplinary issue can find a holistic solution.